Student Engagement and Wellbeing at Public Spaces: A Cross-Contextual Comparative Urban Study - Adhikari, Purnima (Journal of Engineering Issues and Solutions, 2026)
This research investigates student involvement and wellbeing at public spaces, exploring how these environments influence their experiences. Student engagement refers to more than just gathering. It also includes their level of involvement, enthusiasm, and motivation. The research focuses on what attracts students to public areas, what sparks their interest, and how spending their time in such spaces impacts their wellbeing. The study adopts a comparative approach, analyzing two international case studies, Russell Garden (London) and Greenacre Park (New York) alongside three public spaces of Nepal, Patan Durbar Square, Pimbahal and Kamalpokhari. Data were collected through field observations, surveys of 15 students from each national site, and analysis of online public reviews for international sites to understand the use, engagement, and wellbeing outcomes. Findings reveal that students primarily visit these spaces for relaxation, social interaction, discussion with friends and loved ones, leisure activities, and personal reflection. The research highlights differences in design, accessibility, and facilities of public spaces at international and national levels. Based on these insights, recommendations are proposed to improve Nepali public areas, making them more accessible and welcoming to students with complementary facilities like internet, proper seating, public amenities, trees and shading, clean and peace environment if possible, etc.